Recent results on reactions with radioactive beams at RIBRAS (Radioactive Ion Beams in Brazil). (March 2015) - Lépine-Szily, A; Lichtenthäler, R; Guimarães, V; Arazi, A; Barioni, A; Benjamim, E A; de Faria, P N; Descouvemont, P; Gasques, L R; E; Leistenschneider; Mendes, D R; et al.
Abstract: We present a quick description of RIBRAS (Radioactive Ion beams in Brazil), which is a superconducting double solenoid system, installed at the Pelletron Laboratory of the University of São Paulo and extends the capabilities of the original Pelletron Tandem Accelerator of 8MV terminal voltage (8UD) by producing secondary beams of unstable nuclei. The experimental program of the RIBRAS covers the study of elastic and inelastic scattering with the objective to study the interaction potential and the reaction mechanisms between weakly bound (RIB) and halo ( 6 He and 8 B) projectiles on light, medium and heavy mass targets. With highly purified beams, the study of resonant elastic scattering and resonant transfer reactions, using inverse kinematics and thick targets, have also been included in our recent experimental program.